PENGARUH MEDIA PEMBELAJARAN DIGITAL INTERAKTIF TERHADAP PERKEMBANGAN KESADARAN LINGKUNGAN PADA SISWA SEKOLAH DASAR KELAS V - Fadiya, Safa Raisa Nur; Satianingsih, Rarasaning (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to determine the effect of interactive digital learning media on the development of environmental awareness in fifth grade elementary school students. The design of this study is a quasi-experimental study with a post-test only control group design. The population of this study was SDN Dukuh Menanggal 1/424 Surabaya. The sample of this study used fifth grade students from classes V-A, V-B. Data were collected through documentation and tests. The data collection technique was in the form of giving 5 test questions. Data analysis techniques include normality tests, homogeneity tests, and T tests. The findings revealed that there was a significant effect of the use of interactive digital learning media on the development of environmental awareness in fifth grade elementary school students.